Epidemiologic Features of Colorectal Cancer in Zlitan City, Libya - Mohammed Amir Miftah; Mohamed Smeo (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Colorectal cancer (CRC) is one of the most common cancers worldwide. the aim of this study was to investigate the epidemiologic features of CRC in Zlitan city, using data available in oncology outpatient department. Methods. A cross section retrospective descriptive study was conducted to represent the epidemiological features of CRC in Zlitan city of Libya. Results. Males were more affected with CRC than females. About 48% of CRC were within the age range 45 to less than 65 years old, followed by 32% with age group of 65 and younger than 85. Patients with CRC commonly presented with intestinal obstruction. Adenocarcinoma representing 96% of the histopathological types of the tumor, and were most common in rectosigmoid junction. Surgery was the main treatment for colorectal cancer, followed by chemotherapy and radiotherapy. Biopsy was considered as a major step in diagnosis of colorectal cancer. Conclusion. CRC is a disease of non-specific symptoms. It is advised to raise awareness about the need for earlier screening for CRC and the necessity for promoting healthier lifestyle choices as primary prevention.